The application of the N-terminal fragment of pro hormone brain natriuretic peptide (NT proBNP) in cardiac disease risk assessment - Prof R Delport (University of Pretoria, 2013)
Dissertation (MSc (Chemical Pathology))--University of Pretoria, 2012.